1986
DOI: 10.1128/mcb.6.11.3694
|View full text |Cite
|
Sign up to set email alerts
|

Product of Saccharomyces cerevisiae nuclear gene PET494 activates translation of a specific mitochondrial mRNA.

Abstract: The product of Saccharomyces cerevisiae nuclear gene PET494 is known to be required for a posttranscriptional step in the accumulation of one mitochondrial gene product, subunit III of cytochrome c oxidase (coxIII). Here we show that the PET494 protein probably acts in mitochondria by demonstrating that both a PET494-,-galactosidase fusion protein and unmodified PET494 are specifically associated with mitochondria. To define the PET494 site of action, we isolated mutations that suppress a pet494 deletion. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 54 publications
(50 reference statements)
2
69
0
Order By: Relevance
“…3, E and F). Similar experiments with mitochondria of a pet111 and pet494 mutant deficient in translation of Cox2p and Cox3p, respectively (40,41), confirmed that neither mutation interfered with formation of the Atp9p-Cox6p complex. Like the atp10 and mss51 mutants, both the pet111 and pet494 mutants showed a time-dependent decrease during the chase of radiolabel in the high molecular weight complexes seen on blue native gels (not shown).…”
Section: Properties Of the Atp9p-cox6psupporting
confidence: 56%
“…3, E and F). Similar experiments with mitochondria of a pet111 and pet494 mutant deficient in translation of Cox2p and Cox3p, respectively (40,41), confirmed that neither mutation interfered with formation of the Atp9p-Cox6p complex. Like the atp10 and mss51 mutants, both the pet111 and pet494 mutants showed a time-dependent decrease during the chase of radiolabel in the high molecular weight complexes seen on blue native gels (not shown).…”
Section: Properties Of the Atp9p-cox6psupporting
confidence: 56%
“…Direct evidence for the existence of this intermediate was obtained in the present study by analyzing Cox1p intermediates in pet111 and pet494 mutants expressing Cox1p-HAC. Both pet111 and pet494 mutants are COX-deficient due to their failure to translate Cox2p and Cox3p, respectively (31,32). Mitochondrial gene products in each stain were pulse-labeled in organello, and proteins associated with Cox1p-HAC were purified from digitonin extracts with protein C antibody beads.…”
Section: Cytochrome C Is Necessary For Optimal Translation Of Cox1p Bmentioning
confidence: 99%
“…The mutations characterized so far are recessive, thus defining positive-acting products. In a number of cases, it has been possible to show that these products are indeed located inside mitochondria [92,96,97]. Mitochondria1 mutations that allow bypass of the translational block in a number of these pet mutants have been isolated and shown to be deletions of mtDNA, resulting in fusion of the non-coding 5'-leader sequences of one mRNA to the body of another [98 -1011.…”
Section: Translation Vnrna Sdrctionmentioning
confidence: 99%